HISTORICAL AND SOCIAL BASIS FOR THE SPREAD OF ISLAM IN KOREA - Odiljon Ernazarov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides an overview of the socio-political and religious-spiritual atmosphere on the eve of the spread of Islam in Korea, the history and stages of the initial relationships between the Korean and Muslim peoples, the formation of Islamic communities in the country, and their assimilation into the local culture.